2002
DOI: 10.1038/sj.leu.2402446
|View full text |Cite
|
Sign up to set email alerts
|

Unique molecular and cellular features of acute myelogenous leukemia stem cells

Abstract: It is well known in the field of acute myelogenous leukemia (AML) that many different translocations and genetic aberrancies are found with the various forms of the disease. Indeed, specific translocations are often associated with disease subtypes that manifest themselves through the accumulation of immature myeloid cells at varying stages of differentiation. Moreover, the differentiation state of myeloid blast populations has been utilized as a means of categorizing different AML subtypes (French, American, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 46 publications
1
74
0
1
Order By: Relevance
“…Recent studies clearly indicate a central role for LSCs in the pathogenesis of AML and emphasize the need to develop treatment strategies that specifically target this rare population (12). Equally important, it is necessary to identify approaches that minimize toxicity to the normal HSC, which is required to sustain all blood-cell lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies clearly indicate a central role for LSCs in the pathogenesis of AML and emphasize the need to develop treatment strategies that specifically target this rare population (12). Equally important, it is necessary to identify approaches that minimize toxicity to the normal HSC, which is required to sustain all blood-cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is attractive to speculate that failure to sustain durable remission may be due to a drug-refractory͞resistant malignant stem cell population. Given the potentially critical role of stem cells in both the genesis and perpetuation of AML, recent studies have attempted to better characterize LSC properties (10)(11)(12). Notably, although the immunophenotype of LSCs is similar to normal hematopoietic stem cells (HSCs; CD34 ϩ , CD38 Ϫ , HLA-DR Ϫ ), there are at least three antigens with expression that is known to vary in malignant cells: CD90, CD117, and CD123 (7)(8)(9).…”
mentioning
confidence: 99%
“…Functional studies in human acute myelogenous leukemia have conclusively shown the existence of a small population of leukemic stem cells that are capable of initiating leukemic growth following transplantation into immune-deficient mice (6)(7)(8). The malignant phenotype is a result not only of the chromosomal translocation but also of the complex interactions of the molecular events caused by these chromosomal translocations with the endogenous expression profile/proteome of the transformed cell.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Akt or protein kinase B (Akt/PKB), a serine/threonine protein kinase, has emerged as a crucial regulator of widely divergent cellular processes, including apoptosis, proliferation, differentiation and metabolism. Phosphorylation at the threonine residue-308 (pThr308) and serine residue-473 (pSer473) occurs in response to diverse stimuli, such as hormones, growth factors and extracellular matrix components.…”
Section: To the Editormentioning
confidence: 99%